2007
DOI: 10.1029/2006jb004711
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of the damage zone with fault growth in sandstone and its multiscale characteristics

Abstract: We document the formation and evolution of the damage zones associated with strike‐slip faults in porous sandstone, through detailed field and statistical studies of faults of increasing slip magnitudes. The faults initiate as sheared joints with discontinuous damage zone located primarily at fault tips and fault surface irregularities. With increasing slip, the damage zone develops by progressive fracture infilling and is organized into two components with different characteristics. The first of these compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(66 citation statements)
references
References 55 publications
3
63
0
Order By: Relevance
“…The widths of the stepovers, which are expressed by a negative relief, define approximately the fault zone width varying from 30 to 150 m at the surface. These observations are consistent with the inferred dominant left-lateral slip component across the fault zone and its growth by the linkage of neighboring segments similar to those described by other authors at various locations (Cartwright et al 1995;de Joussineau and Aydin 2007;Aydin and Berryman 2010).…”
Section: Discussionsupporting
confidence: 92%
“…The widths of the stepovers, which are expressed by a negative relief, define approximately the fault zone width varying from 30 to 150 m at the surface. These observations are consistent with the inferred dominant left-lateral slip component across the fault zone and its growth by the linkage of neighboring segments similar to those described by other authors at various locations (Cartwright et al 1995;de Joussineau and Aydin 2007;Aydin and Berryman 2010).…”
Section: Discussionsupporting
confidence: 92%
“…Such vegetation-induced biases may also be a factor that contributes to the observed inconsistency of power law scaling of fracture lengths over different length scales (Nicol et al 1996;de Joussineau and Aydin 2007;Davy et al 2010). Actually we can also see from Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Cowie & Scholtz [26] observed from field data that the size of the breakdown zone scales with the length of the fault, therefore that energy loss per unit fault area should also scale with fault length. Additional laboratory experiments [23,27] and field studies on natural faults [20,[28][29][30][31] also indicated that the width of damage zone increases with fracture length. As pointed out by Nielsen et al [32,33], this offers an interpretation for the apparent discrepancy between fracture energy in large earthquakes (estimated from seismology), and fracture energy resulting from frictional weakening under seismic slip conditions (measured in laboratory experiments).…”
Section: Challenging Observations (A) Dissipation: Is It Only Friction?mentioning
confidence: 94%